Model tests of bending and torsional deformations of thin-walled profiles stiffened with elements made in 3D printing technology. (December 2020) - Kosiń, M.; Major, I.; Major, M.; Kalinowski, J.
Abstract: The paper presents the benefits of using 3D printing technology as an effective way to increase the rigidity of thin-walled bars subjected to non-free torsion. The first part of the article concerns bending and torsion testing of C thin-walled unstiffened and longitudinally stiffened profiles. The proprietary solution made with 3D printing technology was used as the longitudinal stiffening. The impact of a stiffener used on bending – torsional displacements in selected profile sections was assessed. The results of experimental research and numerical analysis made with the finite element method were compared. Based on numerical simulations and experimental tests carried out, it can be stated that the stiffener that was used increases the flexural and torsional stiffness of thin-walled profiles. In the second part of the work, in order to present the legitimacy of the discussed topic, the impact of the disassembly of the outer plating in the storey of a single-story structure of a single-family building made of light steel framework technology on its stability is shown. For this purpose, three various calculation were assumed for the adopted object, whose models were subjected to numerical analysis by the finite element method. The analysis took into account possible charges to occur in accordance with the regulations in force in Poland. Due to the analysis of the building model without stiffening plating on the ground floor, it was confirmed that the displacement limits specified in the standards were exceeded. The study showed that the self-wedging assembly insert developed in 3D printing technology developed by the authors is an effective way to increase the rigidity of non-free torsion of C-type steel thin-walled profiles and is used in renovation and repair works when there is a need to stiffen a building block following the removal of wall sheathing.